2003
DOI: 10.1002/app.12620
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and application of immobilized lipase enzyme on different radiation grafted polymeric films: Assessment of the immobilization process using spectroscopic analysis

Abstract: Lipase has been immobilized onto different films, polypropylene and poly(tetrafluoroethylene-perfluroro-propyl vinyl ether) using glutalaradehyde as a crosslinker. Differential scanning calorimetery, Fourier transform infrared spectroscopic, x-ray diffraction, and scanning electron microscopy measurements were carried out to confirm the structure of the polymer films as well as the immobilization process of the enzyme onto the polymeric carrier. The activity and stability of the resulting biopolymers produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
2
6
0
2
Order By: Relevance
“…It was observed that the structure of modified PVA allows the local pH value to be maintained at a level different from the pH of the external medium. 23,24 The immobilized glucose oxidase preparations exhibited high stability against inactivation caused by various water-miscible organic solvents, dioxan, acetone and tetrahydrofuran. Figure 4 shows that the enzyme immobilized using the covalent binding technique [GOD-immobilized onto epichlorohydrin-agarose (Prep II)] exhibited more resistance to solvent-induced inactivation compared with the other preparation prepared by the radiation-entrapment technique [GOD-immobilized in PVA/PAAm hydrogel (Prep I)].…”
mentioning
confidence: 99%
“…It was observed that the structure of modified PVA allows the local pH value to be maintained at a level different from the pH of the external medium. 23,24 The immobilized glucose oxidase preparations exhibited high stability against inactivation caused by various water-miscible organic solvents, dioxan, acetone and tetrahydrofuran. Figure 4 shows that the enzyme immobilized using the covalent binding technique [GOD-immobilized onto epichlorohydrin-agarose (Prep II)] exhibited more resistance to solvent-induced inactivation compared with the other preparation prepared by the radiation-entrapment technique [GOD-immobilized in PVA/PAAm hydrogel (Prep I)].…”
mentioning
confidence: 99%
“…Also, the pH optimum of α‐amylase did not change on immobilization. This implied that the immobilization of α‐amylase did not affect the enzyme‐active site 2…”
Section: Resultsmentioning
confidence: 98%
“…Radiation‐induced graft copolymerization is a well‐known method used to introduce functional groups into different polymer materials with specially selected monomers. There have been several reports on the use of radiation graft copolymerization of polar monomers onto polymer films to obtain hydrophilic properties for versatile applications 1–5. Grafting copolymerization performed by the radiation method is one useful method because of its uniform and rapid creation of active radical sites 6, 7.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoporous poly( N ‐ isopropylacrylamide) (PNIPAAm) membranes have been fabricated in glass microchannels to substantially enrich and purify nucleic acids through photopatterning technology . Lipase has been immobilized onto different polymeric films, such as polypropylene and the process have been assessed by spectroscopic analysis . Polymeric films in a microchip are useful for high‐density enzyme immobilization .…”
Section: Introductionmentioning
confidence: 99%
“…9 Lipase has been immobilized onto different polymeric films, such as polypropylene and the process have been assessed by spectroscopic analysis. 10 Polymeric films in a microchip are useful for high-density enzyme immobilization. 11 Polymer-based materials, including polydimethylsiloxane, poly(methyl methacrylate), polycarbonate and Teflon, have been extensively used to fabricate microchips using photolithography, soft lithography and micromachining using lasers or microdrilling.…”
Section: Introductionmentioning
confidence: 99%